FORMULASI NANOHIDROGEL EKSTRAK DAUN KELOR (Moringa oleifera) DENGAN VARIASI KONSENTRASI CARBOPOL 980 SEBAGAI PERAWATAN LUKA SAYAT - Kristiana, Isha Desty; Noval, Noval; Budi, Setia; Audina, Mia (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2025)
A cut wound is the damage or loss of body tissue due to a sharp object, which can cause bleeding, as well as cause inflammation. Hydrogel is an ideal preparation for wound closure. Nanohydrogel are a development of nanotechnology that has a particle size of 10-1000 nm. Making nanohydrogel preparations requires a gelling agent to obtain a qualified preparation, for example Carbopol 980. Nanohydrogel was made using Moringa leaf extract (Moringa oleifera) as an active substance and made with variations in Carbopol 980 concentration. To evaluate the results of nanohydrogel preparation and determine the effect of variation in Carbopol 980 concentration on moringa leaf extract (Moringa oleifera) nanohydrogel preparation. The method used was experimental with Quasi Experimental design. Simplisia is made into extracts and formulated into nanohydrogel preparations and continued with evaluation. Data were analyzed using One Way Anova. The particle size of moringa leaf extract nanohydrogel preparation was found to be 338 nm. The results of the preparation evaluation showed that moringa leaf extract nanohydrogel with varying concentrations of Carbopol 980 had an effect on the pH, viscosity, and spreadability tests shown in the One Way Anova statistical test (p<0.05). From the evaluation results, the ideal formulation for nanohydrogel preparation is obtained in formula 4 with a concentration of Carbopol 980 of 1%.